Cognition based Service Selection in Semantic Web Service Composition - Kumar, Sandeep; Mishra, R. B. (INFOCOMP Journal of Computer Science, 2008)
Selecting most appropriate service among the available services for performing an activity is one of the important activities of semantic web service composition process. The paper presents a cognitive parameters based model for rating the different service providers based on their cognitive parameters like trustworthiness, capability, commitment, intention, desire, reputation etc. The model covers a wide range of parameters in its rating and provides a feedback system which will affect the reputation of selected service provider.